Unveiling the Growth Trajectory: Agribusiness Value Chain Development in Nepal - Bhandari, Ramesh (GS WOW: Wisdom of Worthy Research Journal, 2024)
This article delves into the development trajectory of the agribusiness value chain in Nepal, emphasizing the sector’s potential and challenges. Nepal’s agrarian economy heavily relies on agriculture, which employs 63% of the population and contributes 27% to the GDP. Despite this, the sector’s growth lags behind population expansion, necessitating a shift from subsistence to commercial farming. The study reviews the literature and employs various analytical methods to understand the current state and dynamics of Nepal’s agribusiness. It highlights the importance of value chain development, as conceptualized by Porter (1985), in enhancing competitiveness, productivity, and cost management. The article discusses theoretical frameworks and the significance of integrating sociological, scientific, and economic components in the value chain. It also addresses the global and national contexts, stressing the need for market-driven strategies, private sector involvement, and policy reforms to promote commercial agriculture. The findings underscore the critical role of value chain development in boosting Nepal’s agribusiness potential, improving farmers’ livelihoods, and achieving sustainable economic growth.